2019
DOI: 10.1007/s00167-019-05503-5
|View full text |Cite
|
Sign up to set email alerts
|

Despite patient-reported outcomes improve, patients with femoroacetabular impingement syndrome do not increase their objectively measured sport and physical activity level 1 year after hip arthroscopic surgery. Results from the HAFAI cohort

Abstract: Purpose Patients with femoroacetabular impingement syndrome (FAIS) are young and middle‐aged persons living physically active lives including sports activities. However, measurements of the physical activity level before and after hip arthroscopic surgery in patients with FAIS using both self‐reported and objective accelerometer‐based measures are lacking. Furthermore, comparing patients with a reference group of persons reporting no hip problems and conducting subgroup analyses investigating changes in physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
(43 reference statements)
2
18
0
Order By: Relevance
“…Similarly, although only seven of the included studies sought to quantify the amount of activity undertaken in specific sports, the negative trends depicted indicate the importance of tracking more than one domain of physical activity. This is reiterated in the findings of Kierkegaard et al [154], with the lack of agreement between objective and subjective reports of activity change. Only a quarter of the studies reported on the activity profile of participants, although information about the type of activity undertaken would be of value in identifying potential barriers and facilitators to physical activity participation post-arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Similarly, although only seven of the included studies sought to quantify the amount of activity undertaken in specific sports, the negative trends depicted indicate the importance of tracking more than one domain of physical activity. This is reiterated in the findings of Kierkegaard et al [154], with the lack of agreement between objective and subjective reports of activity change. Only a quarter of the studies reported on the activity profile of participants, although information about the type of activity undertaken would be of value in identifying potential barriers and facilitators to physical activity participation post-arthroscopy.…”
Section: Discussionmentioning
confidence: 85%
“…One study [154] reported objective measures of physical activity utilising accelerometry. The majority (n = 99, 83%) presented the Hip Outcome Score-sportspecific subscale (HOS-SS, Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…My PhD included studies on patients with femoroacetabular impingement syndrome (FAIS). We performed (1) a systematic review with meta-analysis1 investigating patient-reported outcomes before and after hip arthroscopic surgery in patients with FAIS; and (2) a cohort study in which I investigated patient-reported outcomes, hip muscle strength and physical activity level in 60 patients with FAIS before and after hip arthroscopic surgery 2–5…”
Section: What Did I Do?mentioning
confidence: 99%
“…The cohort study was conducted at Horsens Regional Hospital and Aarhus University in Denmark, where I tested all patients in an isokinetic dynamometer (figure 1)3 4 and attached accelerometers to their thigh in order to monitor daily activity level for 5 days 5. Patient-reported outcomes were collected using the Copenhagen Hip and Groin Outcome Score (HAGOS) 2.…”
Section: How Did I Do It?mentioning
confidence: 99%